2004
DOI: 10.1016/s1476-5586(04)80051-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Survivin in G2/M Cells and Inhibition of Caspase 9 Activity Enhances Resistance in Staurosporine-Induced Apoptosis

Abstract: Survivin, a member of the inhibitor of apoptosis (IAP) gene family, plays an important role in both the regulation of cell cycle and the inhibition of apoptosis, and is frequently overexpressed in many tumor types. In neuroblastomas, the expression of survivin correlates with a more aggressive and histologically unfavorable disease. Survivin is predominantly a cytoplasmic protein that is expressed in a cell cycle-dependent manner, increasing in the G2/M phase of the cell cycle followed by a rapid decline in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…It is reported that Survivin has specific expression during G 2 /M phase of the cell cycle, followed by rapid decline of both mRNA and protein levels at the G 1 phase, and the protein has a half-life about 30 min [12]. Our study revealed that the expression of Survivin in G 2 /M phase was mostly higher among 3 phases, and S phase took the second place, then the G 0 /G 1 phase, which was consistent with the previous study [37][38]. Although LMP1 increase Survivin expression in all the 3 phases, it has more obviously effect on regulating the expression of Survivin in G 0 /G 1 and S phase, which suggested that Survivin may play unusual role in G 1 /S phase.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 91%
“…It is reported that Survivin has specific expression during G 2 /M phase of the cell cycle, followed by rapid decline of both mRNA and protein levels at the G 1 phase, and the protein has a half-life about 30 min [12]. Our study revealed that the expression of Survivin in G 2 /M phase was mostly higher among 3 phases, and S phase took the second place, then the G 0 /G 1 phase, which was consistent with the previous study [37][38]. Although LMP1 increase Survivin expression in all the 3 phases, it has more obviously effect on regulating the expression of Survivin in G 0 /G 1 and S phase, which suggested that Survivin may play unusual role in G 1 /S phase.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 91%
“…However, our data ruled out this possibility. Survivin, a member of the inhibitor of apoptosis gene family, is expressed in a cell cycle-dependent manner, increasing in the G2/M phase of the cell cycle followed by a rapid decline in the G1 phase [26,27]. Recent studies have revealed that quercetin inhibits cell proliferation by causing cell cycle arrest in G2/M phase [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, downregulation of the mitochondrial IAP antagonist Smac/DIABLO is associated with renal cell carcinomas, and overexpression of survivin, another IAP, has been observed in most transformed cell lines and cancers tested to date, as compared with its absence in most normal adult tissues. 12,13 Although there is evidence suggesting an indirect caspase-9 processing interference by survivin, 14 malfunctions of mitotic spindle checkpoint and aberrant progression of transformed cells may be due to non-apoptotic functions of this particular IAP. 15 Association between X-linked inhibitor of apoptosis protein (XIAP) overexpression and poor clinical outcome has been reported for both renal cell carcinomas and acute myelogenous leukemia (AML).…”
Section: Apoptosis As a Defense Strategy Against Tumorogenesismentioning
confidence: 99%